PRESUPPOSITION OF PRESIDENT ERDOGAN’S MESSAGE IN HUMAN RIGHTS DAY ON DECEMBER 10, 2018 - Ratu Nur Auliawanti; Aseptiana Parmawati (IKIP Siliwangi, 2020)
Communication will be impossible if everything had to be defined or explained every time we spoke. Whatever a speaker or writer assume that the receiver of the message already knows is called presupposition. This research analyzed about presupposition of message Recep Tayyip Erdoğan as President of The Republic of Turkey on Human Rights Day, December 10, 2018. The aims of this research are to find out the types of presupposition and identify the most dominant type of presupposition that used by Erdogan. Classification about types of presupposition by Yule (1996) as cited in Tryana & Satelah (2018) used in this research. The researchers analyzed the data with some steps applying the qualitative method, the researchers identifying the scripts of the speech, classifying the utterances into presupposition and categorizing them based on the types of presupposition. After that, counting the types of presupposition in percentage. As the result, The existential presupposition is the dominant type in Erdogan’s speech with the percentage 56,67% and followed by lexical and factive in the second and third position. Keywords: Presupposition, Types of Presupposition, Recep Tayyip Erdoğan